COMPARE OF ARTERIAL HYPERTENSION THERAPY WITH AMLODIPIN, METOPROLOL AND ENALAPRIL MALEATI IN PATIENTS OF OLDER AGE GROUP WITH HYPOTENSION ORTHOSTATIC REACTION - GarkaviyP.А. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
265 AH patients investigated. 98 patients were taking CA, 85 – BB, 82 – ACE. Hydrochlorothiazide was added to one of the drugs if hypotensive effect was insufficient. BP was measured before, within 1, 2 weeks, 1,3 and 6 months after treatment. Two groups were identified during the tilt test: group 1 – normotensive orthostatic reaction (NOR), BP changes from -5 mmHg to +20 mmHg, and group 2 – hypotensive orthostatic reaction (HOR) – 20 mmHg and more SBP decrease and/or 10 mmHg and more DBP decrease. According to our data all three drugs effectively decreased BP, but the dynamics and grade of decrease varied. CA had the most powerful hypotensive effect, decreasing SBP and DBP already on the 1-st week of drug intake, especially in patients with HOR, both in clinostasis and orthostasis. CA therapy increased frequency of HOR on DBP on 5%. BB had less powerful hypotensive effect and in patients with HOR gradually decreased both SBP and DBP in clinostasis, and markedly in orthostasis. Within 6 months of treatment BB decreased SBP and DBP in patients with HOR in clinostasis in the lowest extent, and in larger extent in orthostasis. BB therapy increased frequency of HOR on SBP on 5%, and on DBP on 8%. ACE inhibitors had smooth hypotensive effect, seen after 1-st week of intake. Maximal temps of SBP and DBP decrease was seen in patients with HOR during 1-st – 2-nd weeks of treatment, both in clinostasis and orthostasis. During the first-second week period of treatment with ACE frequency of HOR increased on SBP from 17% to 24% and on DBP from 14% to 17% with further tendency of HOR frequency decrease to 21% on SBP and to 16% on DBP within 6 months. Out of three groups of hypotensive drugs (CA, BB, ACE) probability of HOR progressively increased when using CA and BB, and only when using ACE inhibitors increased temporarily.